2014
DOI: 10.1111/ijd.12401
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccine acceptance among young men in Bangalore, India

Abstract: Background Human papillomavirus (HPV) is the most common sexually transmitted infection in the world. It can lead to anogenital, cervical, and head and neck cancer, with higher risk of malignant disease in patients with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) patients. In India, 73,000 of the 130,000 women diagnosed with cervical cancer die annually. Gardasil®, a vaccine available against HPV types 6, 11, 16, and 18, is approved for use in women in India but not men. A back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
(28 reference statements)
0
13
0
6
Order By: Relevance
“… 17 A survey among young men visiting a dermatology clinic showed that there was a high level of HPV vaccine acceptance (83%), claiming that barriers to vaccination were mainly the cost and potential side effects, while a physician’s recommendation was the main facilitator. 18 Trust, knowledge, regard, and loyalty are four main elements in a physician–patient relationship. 19 For instance, the Guidance-Cooperation Model entails that the physician is placed in a position of power due to having the medical knowledge that the patient lacks on HPV infections.…”
Section: Discussionmentioning
confidence: 99%
“… 17 A survey among young men visiting a dermatology clinic showed that there was a high level of HPV vaccine acceptance (83%), claiming that barriers to vaccination were mainly the cost and potential side effects, while a physician’s recommendation was the main facilitator. 18 Trust, knowledge, regard, and loyalty are four main elements in a physician–patient relationship. 19 For instance, the Guidance-Cooperation Model entails that the physician is placed in a position of power due to having the medical knowledge that the patient lacks on HPV infections.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to present study Belani HK et al, in a study done in Bangalore concluded that high cost of the HPV vaccine acts as a barrier to vaccination (53%). 16 Because of the present high cost of the vaccine the affordability and accessibility of these vaccines is a major concern for a mass vaccination program in developing countries like India. But several studies found that there was no association between income and acceptance and major deterrents found in their study were concern about too many vaccinations, vaccine side effects, worry about increasing promiscuity.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 77 papers and one dissertation were eligible for analysis and were listed in the order of publication years. [171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273747576777879808182838485868788899091929394] The review process is explained in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The studies consist of different populations such as women and men from different community groups[17202425313235394143454751616669717379808586909293]And attended clinics[2729425259676872757682]Students (nursing/medical/paramedical/nonmedical)[3840464850565860646974818389]Health-care providers (doctors, nurses, and other health workers);[1828365354555657626365667778889194] migrated Indians;[1921262730333437498487] and cervical cancer patients. [23]…”
Section: Methodsmentioning
confidence: 99%